The Hidden Cost of Minimum Energy Efficiency Standards - Sébastien Houde; Tobias Wekhof (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
Minimum standard regulations for energy-using durables have long been suspected of having hidden costs: quality improvements in the regulated dimension reduce quality in other dimensions. We substantiate this claim for the U.S. clothes washer market, which has become a notorious example of the hidden cost phenomenon. We find that overall quality increased from 2001 to 2011, and these gains were primarily driven by improvements in energy efficiency. Quality in the non-energy dimensions declined or remained constant after the major standard change. These hidden costs, however, were quickly offset by energy-efficiency improvements in the new models.
Keywords: Q48; Q55; L51; L68; D12; 330; minimum quality standard; hidden cost; energy efficiency regulations; appliance market; ex post analysis